Interações de agentes antifúngicos e antibacterianos frente a Cryptococcus neoformans antes e após indução capsular - Rossato, Luana (2013)
The genus Cryptococcus consists of encapsulated yeasts that cause mainly cryptococcal meningoencephalitis in immunocompromised patients. This mycosis shows high percentage of morbidity and mortality. The fault is not the recommended therapeutic conveniently clarified and, concerning the susceptibility of the fungus to the antifungal, resistance detected in vitro is less frequent than the therapeutic failures. At this juncture, we discuss two aspects: a) considered the presence of the capsule in susceptibility testing, and b) evaluated combinations of conventional antifungal agents (amphotericin B, fluconazole and flucytosine) as well as associations of amphotericin B with antibacterial (azithromycin, daptomycin, linezolid, minocycline, tigecycline and trimethoprim) against 30 isolates of Cryptococcus neoformans. Susceptibility tests to each of the antimicrobial agents and the combinations were performed based on the protocol M27-A3 (CLSI, 2008), with adaptations to ensure the growth of the capsule. Combinations evaluated outside the model "checkerboard". The minimum inhibitory concentrations (MICs) of antifungal agents were higher outside the capsule group (Group II) than in the group without inducing capsular (group I); alone, antibacterials showed no antifungal activity groups studied. Among the combinations of antifungal drugs, showed that amphotericin B + flucytosine has been demonstrated that the highest percentage of synergism against encapsulated isolates (group II), which confirms what is observed in clinic. In the combinations of amphotericin B with antibacterial observed differences in activity: the group without inducing capsular (group I) amphotericin B +minocycline and amphotericin B + tigecycline showed higher percentages of synergism, in group II the best results of synergism were observed for combinations anfhotericin B+linezolid, and anfhotericin B+tigecycline.